2009
DOI: 10.1097/fpc.0b013e328330eeca
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel polymorphisms in the basal promoter of the human transporter, MATE1

Abstract: Human multidrug and toxin extrusion member 1, MATE1 (SLC47A1), plays an important role in the renal and biliary excretion of endogenous and exogenous organic cations including many therapeutic drugs. In this study, we characterized the transcriptional effects of five polymorphic variants and six common haplotypes in the basal promoter region of MATE1 that were identified in 272 DNA samples from ethnically diverse U.S. populations. We measured luciferase activities of the six common promoter haplotypes of MATE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 29 publications
1
41
1
Order By: Relevance
“…The mutations G64D and V480M caused the expression abolition in membranes, resulting in a complete loss of function. Moreover, polymorphisms in the promoter and 5 0 UTR region of MATE1 were reported to decrease transcriptional activity with respective allelic frequency of 3.7% and 23.1-44.5% [23,28]. The SNP rs2289669 is located in the 10th intron of the SLC47A1, and this SNP does not code for an amino acid change.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mutations G64D and V480M caused the expression abolition in membranes, resulting in a complete loss of function. Moreover, polymorphisms in the promoter and 5 0 UTR region of MATE1 were reported to decrease transcriptional activity with respective allelic frequency of 3.7% and 23.1-44.5% [23,28]. The SNP rs2289669 is located in the 10th intron of the SLC47A1, and this SNP does not code for an amino acid change.…”
Section: Discussionmentioning
confidence: 98%
“…Previous study suggested that metformin was a substrate for MATE1 and MATE1 protein mediated transcellular transport of metformin in vitro [21,22]. Meanwhile, novel polymorphisms in MATE1 were reported to affect the expression level and transport function of MATE1 in human kidney, ultimately resulting in variation in metformin disposition and response [23,24]. The oral absorption, hepatic uptake and renal excretion were considered to be key determinants of the glucose lowering response to metformin [25].…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, a common mutation in the promoter region of the MATE1 gene (T>C, SNP rs2252281) is associated with improved response to metformin in T2DM patients (greater A1C reduction) as well as in healthy volunteers (greater glucose-lowering effect)[22]. Functional studies demonstrate that the T>C mutation in the promoter region of the MATE1 gene alters the binding affinity for MATE1 transcription factors (i.e., activator AP-1 and repressor AP-2rep), which reduces MATE1 mRNA expression levels in in vitro assays [26]. Although an effect of genetic variants in MATE1 on human pharmacokinetics has not been observed, these studies suggest that MATE1 plays an important role in the distribution of metformin to target tissues as well as in the glycemic response to metformin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reference sequence of the assayed promoter is typically used as a baseline to compare the promoter activity of nucleotide variants [19]. …”
Section: Methodsmentioning
confidence: 99%